Efektivitas Peraturan Mahkamah Agung Nomor 1 Tahun 2019 Tentang Sidang E-Litigasi Dalam Penyelesaian Sengketa Perdata Di Pengadilan Negeri Bireuen - Risda Elvira; Dian Eriani; Ade Soraya; Munawir; Andi Lesmana (Ameena Journal, 2026)
Electronic court proceedings (E-Litigation) constitute a recent innovation introduced by the Supreme Court of the Republic of Indonesia to provide judicial services in processing and adjudicating cases through the use of information and communication technology. The implementation of E-Litigation is expected to contribute to the realization of the principles of simple, expeditious, and low-cost justice. However, this innovation may also potentially lead to new violations of several fundamental principles of civil procedural law. Based on the background described above, this study formulates two main research questions: (1) How effective is the implementation of E-Litigation hearings in resolving civil disputes at the Bireuen District Court? and (2) What obstacles are encountered in the implementation of E-Litigation hearings in resolving civil disputes at the Bireuen District Court? This study employed an observational research or survey method, in which data were collected from respondents through interviews and questionnaires. In terms of its nature, this research is descriptive, as it seeks to present the actual facts concerning the implementation of E-Litigation. The findings indicate that E-Litigation hearings in resolving civil disputes at the Bireuen District Court have contributed to the establishment of professional, transparent, accountable, effective, efficient, and modern case-management services. Nevertheless, several obstacles remain in its implementation. First, substantive obstacles arise because the implementation of Supreme Court Regulation Number 1 of 2019 has altered several important provisions previously regulated under the HIR and RBg, which had traditionally served as procedural guidelines in district courts. Second, technical obstacles include the limited public understanding of electronic court procedures and the inadequate availability of internet access across all segments of society.